Learning Needs Analysis of Collaborative E-Classes in Semi-Formal Settings: The REVIT Example - Mavroudi, Anna; Hadzilacos, Thanasis (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2013)
Analysis, the first phase of the typical instructional design process, is often downplayed. This paper focuses on the analysis concerning a series of e-courses for collaborative adult education in semi-formal settings by reporting and generalizing results from the REVIT project. REVIT, an EU-funded research project, offered custom e-courses to learners in several remote European areas and received a ‘best practice’ distinction in social inclusion. These e-courses were designed and developed for the purpose of providing training in aspects of the learners’ professional domains related to the utilization of information and communication technologies. The main challenge was to prove that it is possible and economically feasible to provide meaningful training opportunities via distance education, by utilizing existing infrastructure (“revitalizing schools”) and by making use of modern digital technology affordances coupled with suitable distance learning techniques and Web 2.0 tools. ADDIE, the generic instructional systems design model, enhanced with a rapid prototyping phase, was put forth in order to allow stakeholders to interact with a prototypical e-course, which served as an introductory lesson and as a reference point, since its evaluation informed the design choices of all subsequent e-courses. The learning needs approach adopted in REVIT combined learner analysis, context analysis, and needs analysis into a coherent analysis framework in which several methods (observation, estimation, document analysis, survey, and dialogue) were exploited. Putting emphasis on the analysis phase and decoupling the design from the delivery of the e-courses facilitated adaptation and localization. Adaptation and localization issues concerning the adoption of the REVIT distance learning framework, taking into account the socio-cultural and pedagogical context, are discussed. A central result reported is that the analysis phase was crucial for the success of the whole endeavour and that carrying it out properly is not straightforward or easy. The analysis framework presented in this paper could be useful in other similar e-learning situations whose “educational-identity” also involves distance and adult learning in a semi-formal setting.